PIROLISIS LAMBAT CAMPURAN CANGKANG SAWIT DAN PLASTIK DENGAN KATALIS ZEOLIT ALAM - Novan Yuda Wardana; Novi Caroko; Thoharudin Thoharudin (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
This research purposes to find out the characteristic of slow pyrolysis of palm kernel shell and plastic derived from waste grocery bags mixtures with the catalyst addition. Palm kernel shell was mixed with plastic in the persentages of 0%, 10%, 20% dan 30%. The mixtures of palm kernel shell and plastic were feeded in the fixedbed pyrolyzer with the natural zeolite as catalyst. Pyrolyzer was heated and controlled in the temperature of 400oC, 450oC and 500oC. Vapor produced by pyrolysis process was condensed by seperated water cooling. Liquid condensation was collected and measured its weight then analyzed by using GCMS to determain the composition of bio-oil formed from this processes. The research results that the higher temperature pyrolyzer the higher conversion of palm kernel shell and plastic mixtures is by reducing char product. The addition of natural zeolit as catalyst affects in the increase of phenol, alkane and alkene compounds with the reduction of acid compounds.